Perceptions and treatment of sexual abuse victims and perpetrators - Vines, Rebecca (2019)
This thesis explored perceptions of rape and the treatment of sexual abuse victims and a perpetrator. An empirical research study examined whether perceptions of rape were influenced by prior victim-perpetrator relationship, the reason for ex-partner relationship break down and hostile and benevolent sexism. Participants were significantly more likely to take victim supportive attitudes when the relationship ended because the perpetrator was physically violent compared to when the perpetrator was verbally abusive, the victim had an affair, and the victim relocated. Participants with higher hostile and benevolent sexism scores were more likely to hold victim blaming attitudes. A critique of the Ambivalent Sexism Inventory (ASI) is presented. The available evidence provides a mixed view of the tool. The ASI’s validation sample predominantly included white students from Massachusetts and the ability to meaningfully interpret scores was limited as no normative data was provided in studies standardising the tool. The ASI demonstrated good internal consistency and strong convergent validity. A systematic review investigated the effectiveness of psychological interventions to alleviate distress in adult survivors of childhood sexual abuse. The findings demonstrate psychological interventions are superior to no treatment in alleviating certain types of distress in adult victims of childhood sexual abuse, with a notable reduction in post-traumatic stress disorder symptoms. A case study is presented detailing the assessment of a 19-year-old male who sexually offended against a child. The case study details the first term of a community group intervention. After the first term, the client’s Locus of Control remained in the external range and his risk of re-offending, according to the STABLE-2007, remained ‘moderate’.